2022
DOI: 10.1080/21655979.2022.2048992
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of translocator protein 18 kDa suppressed the progression of glioma via the ELAV-like RNA-binding protein 1/MAPK-activated protein kinase 3 axis

Abstract: Glioma is the most common primary malignant brain tumors in adults. Despite considerable advances in treatment, the clinical outcome remains dismal. Translocator protein 18 kDa (TSPO), an evolutionarily conserved transmembrane protein, has always been found to be elevated in glioma, which predicts a poor prognosis. However, studies on the regulatory network of TSPO in glioma are limited. The Cancer Genome Atlas (TCGA) and our research group cohorts demonstrated that TSPO expression was also highly expressed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…However, since TSPO-PET signals allow prognostication of overall survival 34 , TSPO-PET still adds valuable biomarker features to the toolbox of glioblastoma imaging assessments 35 . These quantitative TSPO-PET data even exceeded the prognostic value of gene expression levels 36 , which could be related to the direct quantification of TSPO receptor abundance instead of indirect mRNA measures. The pilot dataset of in vitro scRadiotracing in patients with glioma already showed feasibility even with small amounts of tissue obtained from biopsy.…”
Section: Discussionmentioning
confidence: 89%
“…However, since TSPO-PET signals allow prognostication of overall survival 34 , TSPO-PET still adds valuable biomarker features to the toolbox of glioblastoma imaging assessments 35 . These quantitative TSPO-PET data even exceeded the prognostic value of gene expression levels 36 , which could be related to the direct quantification of TSPO receptor abundance instead of indirect mRNA measures. The pilot dataset of in vitro scRadiotracing in patients with glioma already showed feasibility even with small amounts of tissue obtained from biopsy.…”
Section: Discussionmentioning
confidence: 89%
“…However, since TSPO-PET signals are associated with survival times in patients with primary and recurrent glioma (38,39), TSPO-PET still adds valuable biomarker features to the toolbox of glioblastoma imaging assessments (40). These quantitative TSPO-PET data even exceeded the prognostic value of gene expression levels (41), which could be related to the direct quantification of TSPO receptor abundance instead of indirect mRNA measures. In general, PET imaging is increasingly used for the assessment of patients with brain tumors, in addition to conventional MRI and provides clinically valuable information (40).…”
Section: Discussionmentioning
confidence: 99%
“…37 However, it is also known that the TSPO expression is high in several tumor cells, including U87MG cells. 38 (S)-11 C-KTP-Me is developed in our laboratory as a specific PET tracer for cyclooxygenase-1 (COX-1), which is a rate-limiting enzyme in the synthesis of proinflammatory prostanoids from arachidonic acid and is proven to be useful detection of neuroinflammation. 25 Since, in U87MG cells, it is reported that the expression of COX-1 is at a very low level, 39 it is highly likely that inflammation and tumors can be distinguishable when using by (S)-11 C-KTP-Me but not by TSPO ligands.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Therefore, developing a new tracer that can distinguish between tumors and inflammation is desired. , In neuroinflammation PET imaging, TSPO PET ligands, such as 18 F-DPA-714 and [ 11 C]­PBR28, are widely used . However, it is also known that the TSPO expression is high in several tumor cells, including U87MG cells . ( S )- 11 C-KTP-Me is developed in our laboratory as a specific PET tracer for cyclooxygenase-1 (COX-1), which is a rate-limiting enzyme in the synthesis of proinflammatory prostanoids from arachidonic acid and is proven to be useful detection of neuroinflammation .…”
Section: Discussionmentioning
confidence: 99%